Kiddiesafe: Enhancing Safety and Cleanliness Awareness in Primary School Students through Game-Based Learning - Megat Aris, Puteri Nurfatini; Mohd Nor, Nor Sofi Adlina; Othman, Azliza (UUM PRESS, 2024)
Health and safety education among children is vital to their overall well-being and development. However, children need to understand health and safety so that they can apply it in their daily lives. In the digital age, modern educational institutions face the challenge of engaging a generation of students accustomed to interactive and visually stimulating content. Therefore, this study explores how the KiddieSafe App, an educational tool infused with game design elements, helps students in primary schools learn issues of safety and cleanliness more effectively. Drawing from the concepts of digital game-based learning and the development of 21st-century skills, the app features bright animations, interactive quizzes, and an interactive interface to help engage young learners. User evaluation using the focus group technique was conducted among Year One primary school children. The children were given sufficient time to explore the App and later they were asked to answer the questionnaire. The finding shows that the KiddieSafe App has the potential to enhance learning outcomes and increase students' engagement. The majority of feedback is positive, thus proving this application to have potential as an effective supplementary educational aid for children, which proves the importance of interactive learning in early childhood education. Future enhancements will focus on content diversity and feedback mechanisms to make the learning experience as enriching as possible